Corporate Social Responsibilities to Employees in Indonesia: Economic Return or Merely Impression Construction? - Dina Madinah; Mara Ridhuan Bin Che Abdul Rahman; Mohd Rizal Palil; Shifa Mohd Noor (Indonesian Journal of Sustainability Accounting and Management, 2024)
This paper aims to investigate the effect of CSR to Employees in Indonesia Companies on economic return and human capital efficiency. There were 297 corporate documents recording companies’ social activities for their employees were analysed using content analysis method. CSR to employees consists of four broad dimensions that include 41 items and economic performance was measured by return on investment, sales growth, employee productivity, and human capital efficiency. Out of eight hypotheses, there are only three are supported. Thus, the findings of the study could not substantively support in favour of the first model stakeholders theory namely economic return model. Rather, it is suggested that CSR to employees follows the second model, which means it just a responding tool to employee requests in order to builds a good external impression. The originality of this study are twofold, first is providing new evidence to stakeholder theory from Indonesia CSR perspective and second is improving the measurement of CSR to employee. The study’s findings should be interpreted with caution. The assessment was based on a content analysis of qualitative data from corporate reports which exposing to inconsistencies of information content interpretation.